(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
World has moved towards the cashless transactions and in this order to using E-money Transaction some countries like Belgium , France, Canada etc. have adopted totally cashless transaction system. I think the first requirement for the cashless transaction is to avoid fake currency and others are easy transaction, transparency, development of E-commerce etc. E-money is the basic pillar of cashless transaction and even the people of progressive country are also adopting very frequently in place of hard cash and during Demonetisation the E-money transaction was the main relief for Indian people and even it was used for purchasing the teas, chhole bhatoore , samosas etc. through the E-money transactions via Paytm etc but due to cases of fraud this system is unable to reach its deserving place. The first Question is, what E-money is so E-money is the short form of the Electronic Money, the money which is stored in Electonic Device/modes or used through electronically with the help of internet computerized Server. Basically E-money can be divide in two parts 1. Card based and 2. Network based. Card based E-Money Includes Debit card, Credit Card, ATM card etc. and Network Based E-money includes Paytm, Proton, BHIM app etc. E-money transaction is need of present era but the safety for its user is also very important because 1. Our Cyber system is not ready to protect completely this type of transaction. 2. Users are not aware for their rights and cyber solutions available to them and 3. Carelessness of the users to provide the opportunities to the cyber-criminal. The use of the E-money is adopting by the people at large but our system like banks government agencies, cyber cells, police etc. are not taking suitable steps as per the ratio and situations. However in order to safety and cyber solutions the Information Technology Act-2000 has been enacted but the lack of skilled officer are also a big problem. In case of Cyber Crime victim can report in the police station under which jurisdiction he reside or where his bank situate or Cyber fraudsters/Criminals use phishing, malware, money mule, sim cloning , card fraud , vishing , ATM Skimming and sometime also fraud committed also by the E-money user.